The lexicon spoken by the university student community: a symbol of identity - Neitsa Elías-Toirac; Ariane Tejera-Martínez; Erín Iyamisel López-Orppé (Universidad de Guantánamo, 2016)
This scientific research has as essential premise the study of lexis. Some theoretical aspects on this particular subject, contributed by scholars, have been taken into account. Likewise, some lexical phrases or phraseologisms enriched by the population´s use are analyzed, taking as a reference the experience of the university community in its daily work.